Pudendal nerve versus Lower Limb nerves electrophysiological abnormalities in diabetics with erectile dysfunction in Baghdad - Al-Hadeethi, Mohammed J.; Mohammed, Najeeb H. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Erectile dysfunction (ED) is the persistent inability to perform and maintain penile erection strong enough for fulfilling sexual interaction. It is caused by autonomic neuropathy, vasculogenic causes, endocrine deficit, drug-induced, psychosocial problems, or a combination of these causes. Objective: This study aims to compare pudendal neuropathy against limb neuropathy in diabetics complaining of erectile dysfunction through electrophysiological studies. Methodology: Eighty-four diabetic males were enrolled in this analytic cross-sectional study presented with erectile dysfunction. All participants were assessed by electrophysiological studies using Bulbocavernosus Induced Reflex to assess the competence of the pudendal nerve. Other nerve studies were used to assess lower limb nerve competence. The study was conducted in Ghazi Al-Hariri Surgical teaching hospital in Baghdad for the period from October 2021 to June 2022. Results: Nerve assessments revealed earlier involvement of the peripheral lower limb nerves in comparison with pudendal nerve. Conclusion: Electrophysiological assessment is a practical test which can be used in identifying neurologic deficit among diabetic patients with erectile dysfunction.